2014
DOI: 10.1016/j.visres.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Brain mechanisms underlying behavioral specificity and generalization of short-term texture discrimination learning

Abstract: In this study, we used high-density event-related potentials (ERPs) to investigate the brain mechanisms underlying behavioral specificity and generalization of short-term learning of texture discrimination task (TDT). Human adults were trained with TDT for a single session of 1.5 h and their ERPs were measured on the following day. Behavioral performance showed that, after a same amount of exposure of the trained and untrained conditions during EEG session, learning effects were specific to the trained backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
(94 reference statements)
1
9
0
Order By: Relevance
“…One might argue that it may be partly due to the fact that, in Experiment 2, half of the participants performed the peripheral task before the central task. There might be some sort of fast or shortterm effects of perceptual learning induced by previous blocks (e.g., Ding, Song, Fan, Qu, & Chen, 2003;Qu, Song, & Ding, 2010;Qu et al, 2014;Vatterott & Vecera, 2012), and this prior experience may account for the fact that previously spatially relevant salient stimuli captured attention to some extent even when they became spatially irrelevant (see also Awh, Belopolsky, & Theeuwes, 2012). To rule out this possibility, in Experiment 3, we only adopted the central RSVP task, keeping the peripheral color cues spatially irrelevant throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…One might argue that it may be partly due to the fact that, in Experiment 2, half of the participants performed the peripheral task before the central task. There might be some sort of fast or shortterm effects of perceptual learning induced by previous blocks (e.g., Ding, Song, Fan, Qu, & Chen, 2003;Qu, Song, & Ding, 2010;Qu et al, 2014;Vatterott & Vecera, 2012), and this prior experience may account for the fact that previously spatially relevant salient stimuli captured attention to some extent even when they became spatially irrelevant (see also Awh, Belopolsky, & Theeuwes, 2012). To rule out this possibility, in Experiment 3, we only adopted the central RSVP task, keeping the peripheral color cues spatially irrelevant throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Whether learning can be facilitated through specific or generalized learning has been controversial [6, 26]. While a collection of studies supports that perceptual learning would be contextually specific [27, 28, 29], others suggest that perceptual learning could be transferred across different types of stimuli [26, 30, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…While a collection of studies supports that perceptual learning would be contextually specific [27, 28, 29], others suggest that perceptual learning could be transferred across different types of stimuli [26, 30, 31, 32]. Such an equivocal phenomenon of perceptual learning is determined by various factors: the duration of training and schedule of the training, the relative familiarity of the two stimuli and task relevance [26]. It was shown that interleaved or less frequent training could decrease the specificity effect as it would reduce the suppressive effect of repeated exposure of the stimuli with similar characteristics [30, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the N2pc was a lateralized component, which was isolated by subtracting the ipsilateral ERP waveform from the contralateral ERP waveform to the targets. The modulation of the N2pc by task set and anticipation has been interpreted as evidence for top-down attentional control Gaspar, Rousselet, & Pernet, 2011;Kiss, Jolicoeur, Dell'acqua, & Eimer, 2008;Qu et al, 2014). In this case, we expect that there might be a significant correlation between anticipatory alpha lateralization/hemodynamic lateralization and subsequent target-elicited N2pc during visual search (Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…The modulation of the N2pc by task set and anticipation has been interpreted as evidence for top-down attentional control Gaspar, Rousselet, & Pernet, 2011;Kiss, Jolicoeur, Dell'acqua, & Eimer, 2008;Qu et al, 2014). By using rapid event-related design, we manipulated on a trial-by-trial basis advance information about the cued visual side in which a target would appear and examined two primary questions regarding the neural correlates of spatial attention.…”
Section: Introductionmentioning
confidence: 99%